The principle of Moderation in the Qur'an, Surah al-Baqarah, Verse 143 - Nurul Istianah Ruddin; Hasyim Haddade; Muhammad Yahya (Global Education Journal, 2026)
Socio-religious polarization, intolerance, and the rejection of religious moderation resulting from the weak theological grounding of the faithful at the grassroots level have triggered serious national tensions. This study aims to extract the principle of moderation in Surah Al-Baqarah, verse 143, through a comparison of classical and contemporary interpretations from the Indonesian archipelago. The research method employs a qualitative literature review using a thematic (maudhu’i) exegetical approach to the interpretations of Al-Tabari, Hamka, and Quraish Shihab. The findings reveal a hermeneutical evolution from Al-Tabari’s classical theological-eschatological framework toward the practical, community-oriented approach of Hamka and Quraish Shihab in the Nusantara region. Specifically, Al-Tabari focuses on justice as a witness to the afterlife; Hamka emphasizes the resilience of the nationalist-religious struggle; while Quraish Shihab highlights the dialogical aspect of social inclusiveness. From this dialectic, a blueprint for the three operational pillars of wasathiyah is formulated: the epistemological pillar (the harmonization of reason and revelation), the practical-ethical pillar (the balance of social rights and obligations), and the socio-cultural pillar (active tolerance based on local wisdom). As a concrete recommendation, the Indonesian Ministry of Religious Affairs, interfaith leaders, and educators must organically integrate this three-pillar operational blueprint into the national curriculum and community outreach modules.